The Effect of Financial Ratios and Company Size on Tax Management in Manufacturing Companies Listed on The Indonesia Stock Exchange in 2019-2022 - Felicia, Felicia; Veny, Veny; Feliciana, Feliciana (DINASTI RESEARCH, 2024)
Tax management is a strategy carried out by company management to manage tax payments so as not to exceed the amount that should be paid. The reason this research was conducted is because there are still many people or companies that apply tax. There are several internal company factors that affect tax management such as Profitability, Leverage, Company Size, and Capital Intensity. This study aims to determine and prove the effect of profitability, leverage, company size, and capital intensity individually and simultaneously on tax management in manufacturing companies listed on the Indonesia Stock Exchange for a period of 4 years, namely 2019-2022. The type of research used is quantitative research. The type of data used is secondary data obtained from www.idx.co.id and the company website. The population in this study are manufacturing sector companies listed on the Indonesia Stock Exchange from 2019-2022. The sampling method used was purposive sampling technique with a total sample size of 58 companies. Data processing techniques using multiple linear regression statistical analysis with the help of the SPSS Version 25 program. The results show that profitability has a negative and significant influence on tax management, leverage and company size have no influence on tax management, and capital intensity has a positive and significant influence on tax management. Simultaneously, profitability, leverage, company size and capital intensity have an influence on tax management.